Association of Single Nucleotide Polymorphisms with Type 2 Diabetes Mellitus within the Punjabi Population: A Case-control Study - Jaswant Kaur; Sahiba Kukreja; Mandeep Kaur; Jaskiran Kaur (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) is influenced by both genetic and environmental factors. The TCF7L2 gene, especially the rs12255372 polymorphism, is linked to a higher risk of T2DM in various groups. However, its effect on the genetically and environmentally unique Punjabi population is not well-studied. Aim: To determine the impact of the TCF7L2 (rs12255372) polymorphism on T2DM in the Punjabi Population, India. Materials and Methods: A case-control study was conducted at Sri Guru Ram Das Institute of Medical Sciences and Research, Sri Amritsar, Punjab, India, from April 2022 to July 2024. The study included 200 participants, divided into two groups: Group I consisted of 100 T2DM patients (cases), while Group II comprised 100 healthy individuals (controls). A range of anthropometric, biochemical, and genetic parameters were assessed, including the genotyping of the rsrs12255372(G/T) SNP using real-time Polymerase Chain Reaction (PCR). Measurements were taken for Fasting Plasma Glucose (FPG), Glycated Haemoglobin (HbA1c), and lipid profiles. Odds Ratios (OR) were calculated and statistical analyses were performed using student’s t-test, with a significance level set at p<0.05. Results: In the present study, cases had significantly higher mean age (47.05±8.76 vs. 37.70±7.19 years, p<0.001) and had higher Body Mass Index (BMI) (27.7±5.8 vs. 21.8±1.6, p<0.001) than controls. Most participants in both groups were aged 41-50. Females were more prevalent in the case group (77 vs 62%). Cases also exhibited higher fasting blood glucose (248.8±82.36 vs 93.56±11.72) and HbA1c (9.7±2.1 vs 5.44±0.37%). The TCF7L2 rs12255372 “T” allele was more prevalent in cases. The GT genotype was more frequent in cases (38%) than controls (24%, OR=1.86, 95% CI 1.01-3.45), as was the TT genotype (4 vs 1%). Triglycerides (TG) were significantly higher in cases (176.0±38.8 vs. 153.76±36.61 mg/dL, p<0.001), with a significant association between high TGs and the rs12255372 GT/TT genotypes in cases (p=0.001). Conclusion: The current study identified a significant correlation between the TCF7L2 gene (rs12255372 (G/T) polymorphism) and an increased risk of T2DM in the Punjabi population of India.